Moderating Effect of Vocational Calling on Firefighters’ Stress and Burnout - Choi, HaeYoun (Fire Science and Engineering, 2020)
Firefighters are exposed to complex stresses resulting from life-threatening risks in the work environment, expanding scope of work, insufficient compensation and support. This study investigated the role of vocational calling in job stress leading to burnout, which impairs mental health and organizational effectiveness. One hundred and ninety-one firefighters (average age, 40.97 years; average career, 13.14 years) participated in the study. Firefighters with a high sense of calling showed lower burnout at both low and high stresses than those with a low sense of calling. In the group with low sense of calling, burnout increased more rapidly as the stress level increased than in the group with high sense of calling. As a psychological resource, sense of calling, which leads to the perception of one’s work as meaningful and purposeful, showed a moderating effect that buffers the effect of stress on burnout.